Cancer preventive mechanisms by exercise: activation of p53 and p53-related IGF-1 pathway regulators - Yu, Miao (Kansas State University, 2016)
Exercise has been previously reported to lower cancer risk through reducing circulating IGF-1 and IGF-1-dependent signaling in mouse skin cancer models. This study is to investigate the underlying mechanisms by which exercise might impact IGF-1 pathway regulated by p53 and p53-related proteins in mouse skin epidermis. Female SENCAR mice were pair fed an AIN-93 diet with or without 10-week treadmill exercise at 20 m/min for 60 min daily. Animals were topically treated with TPA or vehicle control 2 hours before sacrifice and the target proteins in the epidermis were assessed by immunohistochemistry and Western blotting. Under TPA or vehicle treatment, MDM2 was significantly reduced in exercised mice compared with sedentary control. Meanwhile, p53 was significantly increased. In addition, p53 transcription target proteins p21, IGFBP-3, and PTEN were elevated in response to exercise. An interaction between exercise and TPA was observed on the decrease of MDM2 and increase of p53, but not p53 down-regulated proteins. Taken together, exercise appears to activate p53 by reducing MDM2 suppression, resulting in enhanced expression of p21, IGFBP-3 and PTEN that might further induce a negative regulation of IGF-1 pathway and therefore contribute to the observed cancer prevention by exercise in this mouse skin cancer model.
Keywords: Exercise; p53; IGF-1; Skin Cancer Model; MiceCancer Prevention